Formulation of the leaves of Orthosiphon aristatus (Blume) Miquel (Family Labiatae) into a tablet dosage form - Bautista, Jocelyn (Santos)
Orthosiphon aristatus (B1) Miq (Family Labiatae) is one of the 219 Philippine medicinal plants with reported diuretic activity. It is utilized as a tea in Asia and in Europe. While the tea is a convenient form of administering the drug, questions of stability, accuracy of dose, continuous availability, and batch-to-batch uniformity often arise. The aim of this paper was to come up with a stable, safe, and low-cost tablet form utilizing an indigenous starch as excipient. Preformulation data were gathered prior to initial formula screening and a Preformulation Report was prepared. The drug has a pleasant color and odor and a bitter taste. The drug also exhibited good flowability, was relatively stable to heat, light, and moisture, and was compatible with common tablet excipients. Initial formula screening involved varying the amounts of the binder and the diluent in the formula. The granules were evaluated as to their moisture content, flowability and particle size distribution while the tablets were assessed for their hardness, friability, disintegration time, thickness, and appearance. An accelerated stability study was conducted for 3 months to determine any change in the tablet's hardness, friability, disintegration time, thickness, appearance, and thin layer chromatogram. Optimization was done to analyze the results of the initial formula screening and to aid in the selection of the best formula. A tablet formulation consisting of 68.29% powdered leaves of O aristatus, 11.58% binder, 19.12% diluent and 1% glidant was selected, validated and produced on a laboratory scale. Quality control tests were performed on the raw materials, intermediate as well as the finished product. The tablets produced were non-friable, with satisfactory hardness and appearance, and disintegrated in less than 30 minutes. An expiry date of 1 year was assigned based on results of the accelerated stability study conducted for 12 months. (A long-term stability study for 36 months is being conducted to confirm whether a longer expiry date may be assigned to the product). A Master Batch Record for O aristatus Tablet 250 mg was prepared and tablet specification were established.
Available to the general public.
Thesis (Master of Science in Industrial Pharmacy)--University of the Philippines Manila, March 1997.
Keywords: Tableting; Drugs -- Dosage forms; Drug Compounding